Lymphocyte and macrophage subpopulations in pelvic ileal pouches. Issue 10 (October 1991) - de Silva, H J; Jones, M; Prince, C; Kettlewell, M; Mortensen, N J; Jewell, D P
Abstract : This study aimed to characterise the mucosal cellular infiltrate in ileal reservoirs with and without pouchitis (reservoir ileitis). Intraepithelial lymphocyte counts were performed in biopsy specimens obtained from ileal pouches and compared with counts in normal ileum and normal colon. T lymphocyte and macrophage subpopulations were characterised immunohistochemically in pouch biopsy specimens using a panel of monoclonal antibodies. Normal ileum was used as a control. Intraepithelial lymphocyte densities (expressed as intraepithelial lymphocyte/100 epithelial cells) in pouches with and without pouchitis were significantly less than in normal ileum, and approached counts found in normal colon. There was no significant increase in counts even in pouchitis. There were no significant differences in the helper/inducer to suppressor/cytotoxic T cell (CD4:CD8) ratios between normal ileum and pouches with or without pouchitis, either in the epithelium or in the lamina propria. The proportions of RFD9+ (epithelioid cells and tingible body macrophages) and 3G8+ (CD16) macrophages were significantly higher in pouchitis compared with pouches without pouchitis or normal ileum. There were no significant differences between the three groups in the proportions of cells positive for the other macrophage markers (CD68, RFD1-dendritic cells, and RFD7-mature macrophages). The significance of low intraepithelial lymphocyte counts in ileal pouches is unknown, but this may be an adaptive response to the new luminal environment. Since an increase in RFD9+ macrophages occurs in inflammatory bowel disease, but does not occur as a non-specific response to an acute infective process, their presence in pouchitis suggests that effector mechanisms similar to those triggering the original ulcerative colitis may be operating in pouchitis.